Pediatric trauma: Results of a prospective study in a public tertiary hospital (Research, Society and Development, 2021)
Objectives: to determine the clinical-epidemiological profile of pediatric mechanical trauma in a public tertiary hospital in the municipality of Aracaju-SE; describe the characteristics of the trauma such as the mechanism, type and severity; and analyze the outcome of the trauma. Methodology: this is an observational, prospective, hospital-based study based on documentary analysis of data obtained from medical records with records of hospitalized children victims of mechanical trauma. Results: based on the data obtained, of a total of 62 research participants, the male gender was the most affected, with (62.9%) of the total, with the most affected age group being 5 to 9 years old, with (40.3% of cases); 64.5% of the patients arrived at the hospital by their own means, with falls as the main trauma mechanism, 75.8% of the cases. Polytrauma was present in 19.4% of patients. Conclusion: most trauma cases evolved to hospital discharge and there was no need for admission to the ICU. Trauma is not only a serious disease, but a relevant Public Health problem, as it is the main cause of pediatric mortality in developed countries, in addition to determining the presence of transient or permanent sequelae, which, consequently, can cause damage to the physical, social and psychological development of the patient.